Effects of blended learning on EFL college students’ oral communicative competence: a critical review of studies - Zhangli, Wu; Ismail, Lilliati; Ahmad, Norhakimah Khaiessa; Mahfoodh, Omer Hassan Ali; Wang, Xuewen (Academy Publication, 2024)
For EFL learners’ development of oral communication competence in English, computer-assisted instruction has become an indispensable model. In the face of the arrival of the information and intelligence era and the need for regular pandemic prevention and control, blended learning has become a normalized teaching approach. Although there have been some investigations of the effectiveness of blended learning in enhancing college EFL students’ English communication skills, a review article that synthesizes the findings of these studies deserves an urgent attention. Thus, the overall purpose of this research is to review previous studies that have examined the use of blended learning to improve college EFL students’ English communication skills. The anticipated outcomes of this research can uncover the potential benefits of utilizing blended learning for enhancing English oral communicative competence among college EFL students. This article can offer some critical perspectives, suggestions, and consequences concerning the integration of blended learning in the acquisition of English language communication competence among college EFL students.